Sovereign debt in sub-Saharan Africa - (:unkn) unknown (My University, 2025)
The initial concept underlying prior research on sovereign debt in Africa was to assess the feasibility of developing debt profiles and, more specifically, to elucidate the relative significance and the role of three donors: the World Bank, China and other bondholders. The primary conclusion drawn from the analysis was that, despite the prevalence of major trends, each African nation possesses a distinct financial identity, which precludes a simplistic categorisation based on external influences. In this paper, the focus will be on the countries of sub-Saharan Africa to establish the state of their indebtedness, while highlighting the role of the three aforementioned lenders.
Keywords: African Research